2012
DOI: 10.1158/0008-5472.can-11-0307
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with PI3K Inhibitor and Toll-Like Receptor Agonist Induces IFN-γ+IL-17+ Polyfunctional T Cells That Mediate Rejection of Murine Tumors

Abstract: The immunosuppressive microenvironment in tumors hampers the induction of antitumor immunity by vaccines or immunotherapies. Toll-like receptor (TLR) ligands have the potential to treat tumors, but they can exert a mixture of positive and negative effects on inflammation in the tumor microenvironment. In this study, we show that specific small molecule inhibitors of phosphoinositide 3-kinase (PI3K) relieve immunosuppression to heighten the proinflammatory effects of TLR ligands that support antitumor immunity.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 44 publications
6
56
0
Order By: Relevance
“…In our current trial, we have confirmed our previous data, implicating that vaccinespecific CD8 + T cells expanded by the current DC type are IFNγ-producing and lytic (24,33,56,57), cover a wide spectrum of TCR affinities including high-affinity CD8 + T cells capable of killing HLAmatched or autologous melanoma lines, and remain as memory T cells even at prolonged vaccination intervals. We now also demonstrated in accordance with recent reports (58) that the vaccine-specific CD8 + T cells were polyfunctional, a property considered relevant for antiviral (59)(60)(61) and antitumor efficacy (62)(63)(64).…”
Section: Discussionsupporting
confidence: 92%
“…In our current trial, we have confirmed our previous data, implicating that vaccinespecific CD8 + T cells expanded by the current DC type are IFNγ-producing and lytic (24,33,56,57), cover a wide spectrum of TCR affinities including high-affinity CD8 + T cells capable of killing HLAmatched or autologous melanoma lines, and remain as memory T cells even at prolonged vaccination intervals. We now also demonstrated in accordance with recent reports (58) that the vaccine-specific CD8 + T cells were polyfunctional, a property considered relevant for antiviral (59)(60)(61) and antitumor efficacy (62)(63)(64).…”
Section: Discussionsupporting
confidence: 92%
“…In murine DCs stimulated with flagellin in the presence of killed tumor cells, PI3K inhibitors suppressed production of IL-10 and TGFβ while preserving or enhancing IL-12 release (Marshall et al, 2012). In a tumor vaccine model, adoptive transfer of PI3K inhibitor-treated DCs enhanced anti-tumor efficacy and fostered the expansion of effector T cells secreting inflammatory cytokines IFNγ and IL-17 (Marshall et al, 2012). This type of approach holds promise for improving efficacy of DC-based vaccines while avoiding systemic administration of PI3K-mTOR pathway inhibitors.…”
Section: Pi3k In Innate and Adaptive Immunitymentioning
confidence: 99%
“…Interestingly, the combination of the inhibitor with the E7 vaccine was able to enhance the vaccine induced immune control in a TC-1 tumor model, showing that the combined strategy of PI3K inhibition with other immunotherapeutic approaches may act synergistically. Along these lines, synergistic antitumor activity has been observed by combining a class I PI3K inhibitor and the TLR5 ligand flagellin (Marshall et al, 2012).…”
Section: Pi3 Kinasementioning
confidence: 99%